Diagnostic Biopsy Site in Cutaneous Angiosarcoma: Reflections from 3 Cases - Fatimah Zanirah Nordin; Adawiyah Jamil; Low Dy Win; Norli-Marwyne-Mohammed-Noor; Norazirah Md Nor; Lee Bang Rom (Dermatological Society of Malaysia, 2024)
Angiosarcoma is a rare, malignant vascular endothelium neoplasm with poor prognosis. Cutaneousangiosarcoma makes up a majority of its presentation. Diagnosis is often delayed due to the nature ofits clinical presentation. We report 3 cases of cutaneous angiosarcoma to focus on the importance ofbiopsy site selection in securing the histopathological diagnosis.